The Performance Pay Premium: How Big Is It and Does It Affect Wage Dispersion? - Alex Bryson; John Forth; Lucy Stokes (Institute for the Study of Labor (IZA), 2014)
Using nationally representative linked employer-employee data we find one-quarter of employees in Britain are paid for performance. The log hourly wage gap between performance pay and fixed pay employees is .36 points. This falls to .15 log points after controlling for observable demographic, job and workplace characteristics. It falls still further to .10 log points when comparing "like" employees in the same workplace, indicating that performance pay contracts are used in higher paying workplaces. The premium rises markedly as one moves up the wage distribution: it is seven times higher at the 90th percentile than it is at the 10th percentile in the wage distribution (.42 log points compared to .06 log points).
Keywords: J33; 330; wages; wage inequality; performance pay; bonuses